Early fecal microbiota transplantation continuously improves chicken growth performance by inhibiting age-related Lactobacillus decline in jejunum - Qiyao Liu; Muhammad Akhtar; Na Kong; Rumeng Zhang; Yue Liang; Yaqian Gu; Danyi Yang; Abdallah A. Nafady; Deshi Shi; Abdur Rahman Ansari; El-Sayed M. Abdel-Kafy; Syed Umair-Ali-Shah Naqvi; et al. (Microbiome)
Abstract Background At an early age, chickens commonly exhibit a rise in the average daily gain, which declines as they age. Further studies indicated that the decrease in chicken growth performance at a later age is closely associated with an age-related decline in Lactobacillus abundance in the small intestines. Whether inhibiting the age-related decline in Lactobacillus in the small intestine by early fecal microbiota transplantation (FMT) could improve chicken growth performance is an interesting question. Results 16S rRNA gene sequencing revealed a higher jejunal Lactobacillus abundance in high body weight chickens in both two different chicken breeds (yellow feather chickens, H vs L, 85.96% vs 55.58%; white feather chickens, H vs L, 76.21% vs 31.47%), which is significantly and positively associated with body and breast/leg muscle weights (P < 0.05). Moreover, the jejunal Lactobacillus abundance declined with age (30 days, 74.04%; 60 days, 50.80%; 120 days, 34.03%) and the average daily gain rose in early age and declined in later age (1 to 30 days, 5.78 g; 30 to 60 days, 9.86 g; 60 to 90 days, 7.70 g; 90 to 120 days, 3.20 g), indicating the age-related decline in jejunal Lactobacillus abundance is closely related to chicken growth performance. Transplanting fecal microbiota from healthy donor chickens with better growth performance and higher Lactobacillus abundance to 1-day-old chicks continuously improved chicken growth performance (Con vs FMT; 30 days, 288.45 g vs 314.15 g, P < 0.05; 60 days, 672.77 g vs 758.15 g, P < 0.01; 90 days, 1146.08 g vs 1404.43 g, P < 0.0001) even after stopping fecal microbiota transplantation at 4th week. Four-week FMT significantly inhibited age-related decline in jejunal Lactobacillus abundance (Con vs FMT, 30 days, 65.07% vs 85.68%, P < 0.01; 60 days, 38.87% vs 82.71%, P < 0.0001 and 90 days, 34.23% vs 60.86%, P < 0.01). Moreover, the numbers of goblet and Paneth cells were also found significantly higher in FMT groups at three time points (P < 0.05). Besides, FMT triggered GH/IGF-1 underlying signaling by significantly increasing the expressions of GH, GHR, and IGF-1 in the liver and IGF-1 and IGF-1R in muscles along age (P < 0.05). Conclusion These findings revealed that age-related decline in jejunal Lactobacillus abundance compromised chicken growth performance, while early fecal microbiota transplantation continuously improved chicken growth performance by inhibiting age-related jejunal Lactobacillus decline, promoting the integrity of jejunal mucosal barrier and up-regulating the expression level of genes related to growth axis. Video Abstract